Religious fasting increase fat free mass (FFM) and reduce abdominal obesity - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim; Yeim, Liyana (Emerald Group Publishing Ltd., 2012)
Purpose: The purpose of this paper is to evaluate the effect of fasting on anthropometry and body composition in fasting obese and non-obese subjects. Design/methodology/approach: In total, 25 volunteers (male and female) were recruited during Ramadan. Age, sex, weight, height, waist and hip circumference and menstrual cycle status (in case of females) were recorded on day 1, and on day 21 weight and waist and hip circumference were also recorded. Similarly, bioelectrical impedance analysis (BIA) was performed on days 1 and 21 for the assessment of changes in body composition. From weight and height, basal metabolic Index (BMI) was determined. Waist-hip ratio was determined from the waist and hip circumferences. Findings: Weight was significantly (p<0.001) reduced in obese individuals on day 21 and accompanied by significant (p<0.01) reduction in waist hip ratios. BIA showed no significant change in the intra or extra cellular water. However, there has been shift of water between the two compartments and there was a strong positive correlation (r=0.9) between the fat free mass and total body water and negative association (r=-0.9) with total body water. Originality/value: This study indicates that fasting could be a useful tool for the management of body weight without having a major shift in the body composition.